The Effect of Transparency Policies on Shadow Economy: Measurement and Evidence from Korea - Binh, Ki Beom; Park, Myung-Ho; Woo, Seokjin (Journal of Reviews on Global Economics, 2018)
This paper provides a new and simple methodology to examine the relative size of the shadow economy to the official one using the quantity theory of money identity. We measure the shadow economy size in Korea annually. The Korean government has implemented various transparency policy measures to identify the tax source in commercial transactions. We find significant evidence that credit card encouragement and the cash payment receipt system have a negative effect on the shadow economy size.